P–107 Does hematological cancer have the same impact on sperm quality as testicular cancer?. (6th August 2021) - Badalotti, M; Badalotti-Teloken, I; Dornelles, V; Teloken, C; Hentschke, M; Cunegatto, B; Pimentel, E; Maciel, A; Justo, F; Petracco, A
Abstract: Study question: Does hematological cancer have the same impact on sperm quality as testicular cancer before chemo or radiotherapy? Summary answer: Hematological cancer has no impact on sperm quality before treatment. What is known already: The deleterious effects of chemo and radiotherapy on testicular function are well known. Furthermore, testicular cancer causes a negative impact on sperm quality, even before treatment, probably due to local action. Hematological cancer, particularly Hodgkin lymphoma, seems to produce inflammatory alterations in the testis. However, it is not clear if hematological cancer can compromise spermatogenesis, as does testicular cancer. Study design, size, duration: Observational, cross-sectional, retrospective study using data from 360 patients seen at a private infertility clinic between 1992 and 2019 for sperm cryopreservation before treatment. The data were collected from electronic records in a prospective database. Participants/materials, setting, methods: Seminal samples from patients that cryopreserved semen due to hematological or testicular cancer were compared. Sperm analyses were performed according to the 2010's World Health Organization (WHO)'s parameters. Seminal volume, total sperm number, sperm concentration, total and progressive motility, and vitality were analysed. In the hematological group, leukemia and lymphoma, and Hodgkin and non-Hodgkin lymphoma were compared. Student t-tests and Chi-Square were used, considering p < 0.05 statistically significant. Main results and the role of chance: This study included 295 patients with testicular cancer (TEST) and 100 with hematological cancer (HEMAT). Patients that had already started chemo or radiotherapy (4 HEMAT and 12 TEST) were excluded, and 4 HEMAT and 15 TEST were azoospermic or cryptozoospermic (41.7% vs. 53, 0%, p = 0, 792 ). The other parameters were analysed in 92 HEMAT and 268 TEST. The mean age of the HEMAT group was 28.2 years and 27.9 for the TEST group (p = 0, 858). The TEST group had higher rates of oligozoospermia (50.7% vs 31.5%, p = 0.001) and of severe oligozoospermia (29.5% vs 15.2%, p = 0.006) than the HEMAT group. Furthermore, 69.6% HEMAT had normal concentration, compared to 45.9% TEST (p < 0.001). The mean concentration of the HEMAT group was 35 mi/mL, normal according to the WHO's standards, and the TEST group was 12 mi/mL, below the WHO's normal standards (p < 0.001). No difference was found when comparing leukemia and lymphoma, or Hodgkin and non-Hodgkin lymphoma. Limitations, reasons for caution: Besides the fact that this study is retrospective, it also has a small sample size. Furthermore, no analyses regarding sperm morphology were made. Wider implications of the findings: In this study, testicular cancer had a negative impact on spermatogenesis and sperm quality, whereas hematological cancer did not. However, counseling regarding fertility preservation using sperm banking prior to chemo or radiotherapy should be reinforced in all young cancer patients. Trial registration number: Not applicable